Students Intercultural Competence in Their Ability to Communicate from Diverse Cultural Backgrounds - Ratag, Linda Patricia; Hampp, Paula L.; Rombepajung, Paula A.; Syariatin, Nur (English Education Department, 2024)
Intercultural competence is an essential skill for students in today’s globalized educational landscape, particularly in English language learning contexts. This study investigates students’ intercultural competence, focusing on their ability to adapt and communicate effectively across diverse cultural boundaries. Employing a quantitative survey approach, data were collected from 53 university students engaged in English language programs. Findings reveal varying levels of competence: while 35.8% of participants reported ease in adapting to cultural differences, nearly half (49.1%) expressed neutrality, indicating limited confidence or experience. Challenges such as language barriers (62.3%) and unfamiliarity with social customs (20.8%) were identified as significant obstacles. Despite these challenges, students participating in cultural exchange programs or engaging with diverse peers demonstrated enhanced competence, gaining enriched perspectives, improved communication skills, and stronger social bonds. Positive experiences included language acquisition, cultural understanding, and mutual respect. To address gaps, the study recommends integrating intercultural communication training, cultural awareness workshops, and experiential learning programs into curricula. Additionally, fostering supportive environments through mentorship and safe spaces for dialogue is essential. These interventions aim to empower students, equipping them for effective communication and collaboration in multicultural academic and professional settings.